MANAJEMEN PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH ISLAM - Burhanudin Burhanudin; Ari Prayoga; Irawan Irawan (ISTIGHNA: Jurnal Pendidikan dan Pemikiran Islam, 2020)
This study aims to uncover the quality improvement planning, quality improvement control, quality improvement, and the results of improving the quality improvement of SMP Plus Al-Aqsa Sumedang. This study uses the Juran trilogy theory including; planning, controlling and improving the quality of education. The approach used in this research is qualitative with descriptive methods. Data collection techniques used include; observation, interview, and documentation study. The results of the study show that; first, the quality planning carried out at SMP Plus Al-Aqsa namely; the strategic step of analyzing market share needs, formulating the vision, mission, and goals of the institution. Second, quality control is implemented at SMP Plus Al-Aqsa namely; the determination of the work structure and supervision carried out by the principal and the internal quality team. Third, quality improvements carried out at Al-Aqsa Plus Junior High School namely; improvement of infrastructure to support institutional activities, formulate short-term, medium-term, long-term programs, and evaluate and identify specific areas that need improvement. The results of improving quality at SMP Plus Al-Aqsa have an impact on learning processes that are more innovative, student achievement and school achievement, customer satisfaction both internally and externally, and compliance with eight national education standards.